A One Health Approach Molecular Analysis of Staphylococcus aureus Reveals Distinct Lineages in Isolates from Miranda Donkeys (Equus asinus) and Their Handlers - Silva, Vanessa (2022)
This work was funded by the R&D Project CAREBIO2: Comparative assessment of antimicrobial resistance in environmental biofilms through proteomics—towards innovative thera-nostic biomarkers, with reference NORTE-01-0145-FEDER-030101, financed by the European Regional Development Fund (ERDF) through the Northern Regional Operational Program (NORTE 2020) and the Foundation for Science and Technology (FCT). projects UIDB/CVT/00772/2020 and LA/P/0059/2020 funded by the Portuguese Foundation for Science and Technology (FCT). Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.